O uso de estratégias de comunicação no contexto de sala de aula de língua inglesa: um estudo de caso - HEBERLEIN, Maria Carolina Terra (2010)
This is a case study which sought to identify and understand the use of communication strategies in the context of an English classroom in Goiânia, Goiás, Brazil. The interactions among four (4) students of the seventh semester of an English course were observed. The research instruments used in this study were recordings in audio and video and field notes made by the researcher. In addition to this, a sociocultural questionnaire was applied in order to gather more information about the participants. For the data analysis, Tarone‟s taxonomy of communication strategies (1983) was used, which divides the strategies into three (3) main categories (paraphrase, borrowing and avoidance) and nine (9) subcategories (paraphrase: approximation, word coinage and circumlocution; borrowing: literal translation, language switch, appeal for assistance and mime; avoidance: topic avoidance and message abandonment). After identifying and categorizing these strategies found in the data, I analyzed them, observed the interactions in which they appeared and the way they were used. Also, some discussions about relevant issues related to the strategy use were raised, such as: the use of mother tongue in the L2 learning, the way the communicative approach has been understood in the language classrooms, the accuracy belief and the parallel between communication versus accuracy. The kind of research developed was a qualitative case study, which means that the number of participants was restrict (4) and the focus of analysis was on the process through which students went during their learning, and not on its ending. Commonly, this work tried to investigate and portray the way communication strategies are used and problematize issues related to this topic. The specific objectives of this research were to identify and categorize the communication strategies used, analyze their uses and relate them to other issues related to English language teaching as a foreign language. We observed a significant frequency of mixed strategies in the context studied, which reflects learners‟ effort to get various types of support during their interactions.